2021
DOI: 10.32615/bp.2021.023
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical changes during graft union formation in Carya illinoinensis

Abstract: To reveal the physiological and biochemical mechanism underlying graft union formation in pecan (Carya illinoinensis), dynamic changes in content of nutrients, tannin, and phytohormones together with key enzyme activities were investigated 0, 3, 5, 7, 10, 14, 18, 22, 31, and 40 d after grafting (DAG), in homograft unions. During graft union formation, peroxidase (POD) activity increased at 7 -10 DAG compared with that at 0 DAG. Polyphenol oxidase (PPO) activity was higher in grafted than ungrafted pecan seedli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The starch contents of leaf samples were also studied, and it was found that the content reached as high as 60 mgÁg À1 DW. In the case of grafted pecan stem samples from 1-year-old seedlings, a lower sugar content (20-39 mgÁg À1 FW) and higher starch content (30-80 mgÁg À1 DW) were observed by Su et al (2021). These studies proved that when soluble sugars were higher in tissues, the starch contents were lower, indicating a relationship between soluble sugars and starch in tissues.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The starch contents of leaf samples were also studied, and it was found that the content reached as high as 60 mgÁg À1 DW. In the case of grafted pecan stem samples from 1-year-old seedlings, a lower sugar content (20-39 mgÁg À1 FW) and higher starch content (30-80 mgÁg À1 DW) were observed by Su et al (2021). These studies proved that when soluble sugars were higher in tissues, the starch contents were lower, indicating a relationship between soluble sugars and starch in tissues.…”
Section: Discussionmentioning
confidence: 74%
“…Bark soluble sugar increased and wood soluble starch decreased as a response to the freeze. Soluble sugar and starch contents of pecan tissues have been analyzed and reported previously (Kim and Wetzstein 2005;Mel endez et al 2021;Su et al 2021;Taylor 1970;Wood 2014). Taylor (1970) reported that the soluble sugar contents ranged from $46 to 97 mgÁg À1 DW and starch contents ranged from 4 to 23 mgÁg À1 DW from pecan stem sections.…”
Section: Discussionmentioning
confidence: 88%
“…This class of secondary metabolites can be found in many species, although few studies have investigated their role in the grafting process. Tannins are involved in the response to wounding, increasing in content as a part of the plant's defense system when mechanical injuries occur through an upregulation of genes involved in their synthesis [26]. Moreover, previous research on sorghum [27] has demonstrated that an accumulation of tannins has negative effects on the proliferation of callus, limiting the formation of vascular tissues.…”
Section: Tanninsmentioning
confidence: 99%